Musculoskeletal injuries in the military - Cameron, Kenneth L.; Owens, Brett D. (Springer, 2016)
This authoritative reference examines the causes of--and offers workable solutions to--the widespread problem of musculoskeletal injuries among armed forces personnel. Specific chapters on combat, non-combat, training, and fitness injuries shed necessary light on the nature and scope of the epidemic, including impact on active service members and the resulting quality of life issues in veterans.